-(Tourism & It’s Role in Achieving Economic &Social Development- Case Study of Some Arab Countries (K. S. A & Qatar - Haj Ali, Akram Mohammed Ahmed (Journal of Economic, Administrative and Legal Sciences, 2018)
This study aims to highlight the important and important role played by the tourism sector in the full development in all its economic, social and political aspects in the Arab world, within the global economy, as well as highlighting the reality of the contribution of the tourism sector in the economic development process in the Arab world. The study concluded that tourism in the current era is an integrated industry that contributes to the comprehensive development of its various forms in many countries of the world, which have been interested in developing this tourism sector to achieve the optimum economic and social benefits. In contrast to what is happening in the Arab countries, many of which have not benefited from these tourism opportunities and lost tourism resources, and this sector has not been given the best attention or in the comprehensive sense has become a complete neglect of this important sector, and may be due to the adoption of many Arab countries on industries And other resources such as petroleum by a very large percentage. Taking into consideration that the Arab countries have many elements and potential attractiveness of tourism activity from archaeological sites combining the unique Islamic monuments in the world and the distinct geographical locations and beaches of rivers, seas and warm oceans, and environmental awareness stimulated to practice all kinds of tourism activities including desert, mountain, forest and other activities. The study recommended that more efforts should be made to take care of this important economic development sector, especially since many Arab countries need to advance economic development in order to benefit from it as an economic resource first and thus the welfare of their people.